Biomaterials and Biological Parameters for Fixed-Prosthetic Implant-Supported Restorations: A Review Study. (18th January 2022) - Afshari, Aysooda; Mosaddad, Seyed Ali; Alam, Mostafa; Abbasi, Kamyar; Darestani, Meshkat Naeimi
Abstract : Because of the increasing use of dental implants, dental practitioners should understand the treatment and nature of peri-implant diseases (PIDs). This disease is a serious problem of dentistry, regarding epidemiology and therapy. Due to the increase in the practice of implantology as well as the increased number of implants placed every year, the rate of PID has widely increased. Peri-implant mucositis and peri-implantitis, gingivitis, and periodontitis are common clinical manifestations of the disease. PIDs are caused by chronic inflammatory processes in the tissues around an intraoral implant, with increasing incidence, and have become a health concern. Bacterial infections are involved in the pathogenesis of these diseases. The imbalance between the host response and bacterial biofilm results in tissue destruction. New challenges lie in the prevention, treatment, and diagnosis of PIDs. The aim of this overview was to focus on the nature of the disease itself, useful diagnostic criteria, common responsible bacteria, and the prosthetic effects of fixed restorations on the health of the periodontium since recognizing the parameters involved in the development of periodontal and PIDs will play a crucial role in preventing the progression and minimizing the complications of these diseases having a fixed prosthesis.